Governing the Market Economic Theory and the Role of Government in East Asian Industrialization - Wade, Robert (Princeton University Press, 2018)
Published originally in 1990 to critical acclaim, Robert Wade's Governing the Market quickly established itself as a standard in contemporary political economy. In it, Wade challenged claims both of those who saw the East Asian story as a vindication of free market principles and of those who attributed the success of Taiwan and other countries to government intervention. Instead, Wade turned attention to the way allocation decisions were divided between markets and public administration and the synergy between them. Now, in a new introduction to this paperback edition, Wade reviews the debate about industrial policy in East and Southeast Asia and chronicles the changing fortunes of these economies over the 1990s. He extends the original argument to explain the boom of the first half of the decade and the crash of the second, stressing the links between corporations, banks, governments, international capital markets, and the International Monetary Fund. From this, Wade goes on to outline a new agenda for national and international development policy
Description based on online resource; title from PDF title page (publisher's Web site, viewed 23. Nov 2018)
Keywords: Geschichte 1930-1990; Industrial policy -- East Asia; Industrialization -- East Asia; Wirtschaftsentwicklung; Wirtschaftspolitik; Wirtschaft; Außenhandel; Marktwirtschaft; Industriepolitik; Industrialisierung; Staat; Ostasien